Landscape Management among the Guarani of the Atlantic Forest of Misiones, Argentina: the Case of the Syagrus Romanzoffiana (Cham.) Glassman (Arecaceae) Palm Tree - Araujo, Jorge (2021)
The study of the management practices that different Guarani settlements have carried out in the environment over time constitutes one of the objectives of ethnoecology and historical ecology as the way through which these communities obtain forest resources affects landscape settings. In this work, based on a local classification system of the ontogenic stages of the pindo palm tree Syagrus romanzoffiana (Cham.) Glassman (Arecaceae), we study the effects of traditional management practices on the unity of the pindoty landscape - plant communities with a high concentration of this species. We evaluated the degree to which two morphometric variables used in the measurements of woody tree species, diameter at chest height (DBH) and total height (H), explain the local classification. As a result, in the environment of four Guarani settlements (Ita Piru, Kurupayty, Pindo Poty, and Yvyra Pepe Poty), the production of edible larvae favors temporary changes in the pindoty landscape unit since it produces changes in pindo population’s structure – (abundances by class size). In addition, we discuss some aspects of the pindoty units and their anthropogenic nature concluding that their evolution results from the Guarani cyclical cosmological conception.